2019
DOI: 10.1002/ese3.379
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a multistage fractured horizontal well in a tight oil reservoir using an embedded discrete fracture model

Abstract: As an unconventional resource, tight oil reservoirs hold abundant geological reserves and great development potential. However, tight oil reservoirs suffer from high heterogeneity and low permeability. To obtain commercial oil and gas flow, multistage hydraulically fractured horizontal well technology is often adopted. In this paper, an embedded discrete fracture model (EDFM) is adopted to study the fractured reservoir. First, the relationship between the EDFM connection list is studied and its coefficient mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Before the mathematical model is established, the fracture network needs to be characterized explicitly. Many fracture models have been developed in the past few years, such as discrete fracture network model (DFN), discrete fracture model (DFM), and embedded discrete fracture model (EDFM) . In the DFN, fluid flow can only occur in the fracture medium, which means the permeability of the matrix is neglected.…”
Section: Governing Equations For Fracture Flowsmentioning
confidence: 99%
“…Before the mathematical model is established, the fracture network needs to be characterized explicitly. Many fracture models have been developed in the past few years, such as discrete fracture network model (DFN), discrete fracture model (DFM), and embedded discrete fracture model (EDFM) . In the DFN, fluid flow can only occur in the fracture medium, which means the permeability of the matrix is neglected.…”
Section: Governing Equations For Fracture Flowsmentioning
confidence: 99%
“…And there are many models that have been proposed, such as the liner flow model, discrete fracture models, and fractured horizontal well in different outer boundaries, so the readers can utilize the models presented in this paper to analyze the well production performance of different models. Besides, the conceptual model can also be considered in the numerical simulation [82][83][84][85].…”
Section: Geofluidsmentioning
confidence: 99%
“…With the rapid depletion of reservoir energy, the oil production declines rapidly. 23 − 27 To improve the production and recovery factor (RF) of TSTRs, the Tuha Oilfield has conducted a lot of research in the past five years and found that the water huff-n-puff (WHP) technology has great application prospects. 28 − 34 In the pilot test area, a total of 52 wells have been conducted with WHP, and the efficiency rate is 92.3%.…”
Section: Introductionmentioning
confidence: 99%